Uji Aktivitas Antibakteri Ekstrak Etanol Beras Putih (Oryza sativa L.) terhadap Pertumbuhan Bakteri Propionibacterium acnes - Nevida Wiehelmina Fanggidae; Anita Lidesna Shinta Amat; Sangguana Marthen Jacobus Koamesah; Syahrir Syahrir (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Background: Acne vulgaris is one of the most common skin problems and is closely associated with the activity of Propionibacterium acnes. Long-term use of antibiotics may lead to bacterial resistance; therefore, alternative antibacterial agents derived from natural products are needed. White rice (Oryza sativa L.) is known to contain bioactive compounds such as flavonoids, alkaloids, terpenoids, tannins, and saponins, which potentially exhibit antibacterial activity. Objective: This study aimed to evaluate the antibacterial activity of ethanol extract of white rice against the growth of Propionibacterium acnes. Methods: This research was conducted as a laboratory experimental study using a post-test only control group design. The ethanol extract of white rice was prepared by maceration using 70% ethanol. Antibacterial activity was evaluated using the disc diffusion method with extract concentrations of 100%, 50%, 25%, 12.5%, and 6.25%. Clindamycin was used as a positive control, while sterile distilled water served as a negative control. The parameter observed was the diameter of the inhibition zone. Result: The results of phytochemical screening showed that the ethanol extract of white rice (Oryza sativa L.) contains flavonoids, alkaloids, and terpenoids. Antibacterial activity test showed that the ethanol extract of white rice at concentrations of 100%, 50%, and 25% was able to inhibit the growth of Propionibacterium acnes by forming an inhibition zone, while at concentrations of 12.5% and 6.25% no inhibition zone was formed. The highest inhibition zone diameter was found at a concentration of 100%. The ethanol extract of white rice at concentrations of 100% (7.65 mm), 50% (6.77 mm), and 25% (6.15 mm) was able to inhibit the growth of Propionibacterium acnes, and was classified as having moderate inhibition. In contrast, at concentrations of 12.5% and 6.25%, the ethanol extract of white rice did not show any inhibitory activity detected in vitro using the disc diffusion method. The results of statistical analysis showed a p value <0.001, which means there was a significant difference in the diameter of the inhibition zone between the treatment groups. Conclusion: In conclusion, the ethanol extract of white rice exhibits antibacterial activity against Propionibacterium acnes in a concentration-dependent manner; however, its inhibitory effect remains lower than that of clindamycin.